2011
DOI: 10.1103/physrevd.84.027501
|View full text |Cite
|
Sign up to set email alerts
|

Destroying a near-extremal Kerr-Newman black hole

Abstract: We revisit here a previous argument due to Wald showing the impossibility of turning an extremal Kerr-Newman black hole into a naked singularity by plunging test particles across the black hole event horizon. We extend Wald's analysis to the case of near-extremal black holes and show that it is indeed possible to destroy their event horizon, giving rise to naked singularities, by pushing test particles towards the black hole as, in fact, it has been demonstrated explicitly by several recent works. Our analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 36 publications
1
133
0
Order By: Relevance
“…Similar potential violations of (1) have been found for Reissner-Nordström black holes absorbing angular momentum [5], Kerr black holes absorbing charge or angular momentum [6][7][8], and for generic Kerr-Newman black holes [9,10]. However, just as in Hubeny's argument, in order to determine whether these potential violations actually occur, one needs to calculate all contributions to energy that are quadratic order in the relevant parameters of the particle.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similar potential violations of (1) have been found for Reissner-Nordström black holes absorbing angular momentum [5], Kerr black holes absorbing charge or angular momentum [6][7][8], and for generic Kerr-Newman black holes [9,10]. However, just as in Hubeny's argument, in order to determine whether these potential violations actually occur, one needs to calculate all contributions to energy that are quadratic order in the relevant parameters of the particle.…”
Section: Introductionmentioning
confidence: 54%
“…9 If we wish to take Σ 1 to extend infinitely far from the black hole, we would have to take it to null infinity rather than spatial infinity. 10 Note that since mass and angular momentum cannot be radiated away at linear order, we did not need to be careful in our specification of Σ 1 in our first order analysis in order for δM and δJ to represent the perturbed mass and angular momentum of the final black hole.…”
Section: Gedanken Experiments To Destroy a Slightly Non-extremal mentioning
confidence: 99%
“…The possibility of turning a black hole into a naked singularity by accretion of different types of particles was analysed in several theoretical researches, and a variety of conclusions have been proposed: from works finding that an extreme black hole cannot accrete particles that would make its horizon disappear to works that contradict this conclusion by analysing accretion of test particles by nearly extreme black holes (see, for example, Wald 1974a;Hubeny 1999;de Felice & Yunqiang 2001;Jacobson & Sotiriou 2009;Saa & Santarelli 2011, for studies related to Kerr and Reissner-Nordström solutions).…”
Section: Introductionmentioning
confidence: 99%
“…The range of parameter b is given in [3,4]. As shown in [2] the allowed range for the uncharged particle to enter the black hole is given by [3, √ 12].…”
Section: Particle Motion Around Near-extremal Kerr Black Holementioning
confidence: 99%
“…It was also shown that it would be possible to destroy near-extremal Reissner-Nordström black holes with charged test particle [3]. The process of destroying rotating black hole with the charged test particle was investigated in [4]. In all these calculations it was assumed that the test particle follows a geodesic motion and effects of the conservative and dissipative backreaction were ignored.…”
Section: Introductionmentioning
confidence: 99%